2010
DOI: 10.1063/1.3276903
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-normality and nonlinearity of the Navier–Stokes operator on the dynamics of a large laminar separation bubble

Abstract: . The effects of non-normality and nonlinearity of the Navier-Stokes operator on the dynamics of a large laminar separation bubble. The effects of non-normality and nonlinearity of the Navier-Stokes operator on the dynamics of a large laminar separation bubble, 2010, 22 (014102), pp.15. <10.1063/1.3276903>. The effects of non-normality and nonlinearity of the Navier-Stokes operator on the dynamics of a large laminar separation bubble The effects of non-normality and nonlinearity of the two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…The topological changes are found to trigger a rapid transition to an absolute instability. Topological changes in the base flow are also connected with the onset of unsteadiness in separation bubbles investigated by Cherubini et al 15 Vortices may shed via the classic inviscid Kelvin-Helmholtz instability in a free shear layer, where the shear layer rolls up into a sequence of vortices that subsequently detach from the layer. In addition, in axisymmetric jet flow into a quiescent medium, vortex rings are shed via a process termed "pinch-off."…”
Section: A Vortex Shedding Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…The topological changes are found to trigger a rapid transition to an absolute instability. Topological changes in the base flow are also connected with the onset of unsteadiness in separation bubbles investigated by Cherubini et al 15 Vortices may shed via the classic inviscid Kelvin-Helmholtz instability in a free shear layer, where the shear layer rolls up into a sequence of vortices that subsequently detach from the layer. In addition, in axisymmetric jet flow into a quiescent medium, vortex rings are shed via a process termed "pinch-off."…”
Section: A Vortex Shedding Phenomenamentioning
confidence: 99%
“…10 Furthermore, transient growth studies suggest that the optimal perturbation may be in the form of a convective-type instability. For example, Alizard et al 10 and Cherubini et al 15 identify the optimal perturbation for the occurrence of unsteadiness in a separated boundary-layer flow over a flat plate as "convective waves" or a disturbance that is localized near the separation point of the recirculation region and amplified along the shear layer as it convects downstream through a pseudo-resonance of global modes. Blackburn, Sherwin, and Barkley 33 also find that optimal growth dynamics mimic a convective instability in a stenotic flow.…”
Section: A Relation To a Convective Instabilitymentioning
confidence: 99%
“…Several scenarios are possible. Cherubini, Robinet & De Palma (2010) have shown that when an LSB is large enough the modes associated with the shear layer can interact non-normally and nonlinearly to generate self-sustained low-frequency oscillations. Other scenarios are possible, for instance synchronization of flow through a hydrodynamic and/or pressure feedback mechanism (such as the Rossiter mechanism, observed in open cavities) can force the flow at low frequency and enhance a collective interaction mechanism.…”
Section: Future Researchmentioning
confidence: 99%
“…Streaky structures are observed at different scales in transitional and turbulent shear flows (Brandt, Schlatter & Henningson 2004;Hwang & Cossu 2010) and their † Email address for correspondence: s.cherubini@gmail.com origin seems now to be well understood. As conjectured by Landahl (1980) some decades ago, elongated near-wall zones of low and high momentum are created by a mechanism of transient growth of the perturbations known as the lift-up effect, linked to the non-normality of the Navier-Stokes operator (Cherubini, Robinet & De Palma 2010b). Such a mechanism is based on the transport of the mean shear by rolls of streamwise vorticity.…”
Section: Introductionmentioning
confidence: 99%